EKSPLORASI MODEL DIGITALISASI EKONOMI UMKM DALAM MENDORONG KETAHANAN EKONOMI MELALUI TRANSFORMASI SOSIAL DI MALANG RAYA: Digitalisasi Ekonomi, UMKM, Transformasi Sosial, Ketahanan Ekonomi, Inovasi Teknologi - Dina Ekasari, Luh; Himawan Wibisono, Sukarno (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
The digitalisation of the economy is a key factor in improving the competitiveness and resilience of MSMEs, especially in this era of ongoing social transformation. MSMEs in the Greater Malang area face challenges in adopting digital technology, both in terms of access, digital literacy, and infrastructure readiness. Social transformation driven by changes in consumer behaviour, government policies, and technological innovations requires SMEs to adapt in order to survive and thrive. Therefore, this research is crucial for exploring effective economic digitalisation models for SMEs, aiming to strengthen economic resilience amid the ongoing social and economic dynamics. The objective of this research is to identify and analyse economic digitalisation models that can be applied by MSMEs to enhance economic resilience through social transformation. The methodology employed is a mixed-method approach, combining qualitative analysis through in-depth interviews and case studies of MSMEs, as well as quantitative analysis through surveys of MSMEs in Malang Raya. The results indicate that digital transformation influences social transformation, SME economic digitalisation has a significant positive impact on economic resilience, social transformation has a significant positive impact on economic resilience, and SME economic digitalisation influences economic resilience through social transformation.